Zoning Effectiveness of Marine Nature Reserve Conservation Areas (SAP) Raja Ampat Islands Against Coral Reef Protection - Faidlul Qodir; Mauludiyah; Dian Sari Maisaroh; Wiga Alif Violando; Ofri Johan; Idris; Nurliah; Saptono Waspodo (Jurnal Biologi Tropis, 2023)
Raja Ampat Islands have been designated as a Marine Nature Reserve (SAP) since 2014, and community activity in these waters remains high for tourism, fishing and sea transportation activities. All of these activities have the potential to suppress the condition of the coral reefs there. Therefore, it is necessary to evaluate the effectiveness of zoning in terms of social and ecological indicators. This research was conducted using the Underwater Visual Census (UVC) method for coral reef fish and the Underwater Photo Transect (UPT) method for coral cover at a depth of 5-7 m. The set critical threshold value is used to evaluate the success of the zoning taken by interviewing fishermen. The results of the study found that the core zone had unfavorable conditions compared to the other zones. Based on an analysis of ecological indicators, the percentage of coral cover was only 20.9% and an abundance of reef fish of 28 ind/m2. The results of the social analysis of the community, Waisilip Village has the lowest level of compliance with a value of 56%. Meanwhile, 77% of respondents agree with zoning, and only 19% understand the zoning management system. The management of SAP Raja Ampat can be said to be effective by taking into the ecological and social indicators of the community. Increase in the percentage of coral cover in the core zone (0.2%), utilization zone (3.9%), sustainable fisheries zone (0.8%) and cultivation zone (5.7%). Most fishermen have good insight and concern for coral reefs and other aquatic resources.